Financial Crisis, Economic Recovery and Banking Development in Former Soviet Union Economies - Dalia Marin; Haizhou Huang; Chenggang Xu (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2002)
This paper provides a unified theory to explain the onset of the financial crisis in 1998 and the striking economic recovery in Russia and the former Soviet Union afterwards. Before the crisis, the banking sector in these economies was stuck in a development trap in which the banking sector is separated from the real sector of the economy. The separation between the two sectors arises due to a lemons lending market and due to a large government budget. In a lemons credit market firms may find it cheaper to raise liquidity through non-bank finance (trade credits from other firms) rather than through bank finance. As a result non-bank finance may generate an externality on the lending rates of banks. In equilibrium most firms in the economy rely on non-bank finance and the financial sector focuses on trading government securities. The collapse of the treasury bills market in Russia in the financial crisis of 1998 reversed this process and thus acted as a trigger to pull the economy out of the trap. This has led to the strong economic recovery and provided initial conditions for banking development. Empirical evidence with firm level data from Ukraine in 1997 and with country level data for transition economies support the model's predictions.
urn:nbn:de:bvb:19-epub-27-5
Keywords: G3; G2; P34; O16; D82; 330; banking development; institutional trap; trade credit; nonbank finance; finance in emerging market economies